Reference interaction site model study on the anomeric equilibrium of D-glucose in aqueous solution - Miyata, T. (Condensed Matter Physics, 2007)
The anomeric equilibrium of D-glucose in aqueous solution was studied by the extended reference interaction site model (XRISM) theory. In this study, all of the rotational degrees of freedom were considered upon the exocyclic hydroxyl and hydroxymethyl groups, namely 729 stereoisomers for each anomer. The free energy differences between the α and β anomers were calculated from partition functions. The XRISM theory predicts that β-D-glucose is more stable in aqueous solution than α-D-glucose, which agrees with an experimental result qualitatively. It is found that the solvation free energy stabilizes the β anomer more preferably than α, and that the intramolecular electrostatic energy of the β anomer in solution is remarkably higher than that of α. The β anomer in aqueous solution would favor an interaction with water molecules through hydrogen bonds, compared to the α anomer.